2009
DOI: 10.1111/j.1365-2249.2009.04051.x
|View full text |Cite
|
Sign up to set email alerts
|

Calcineurin inhibitors affect B cell antibody responses indirectly by interfering with T cell help

Abstract: SummaryIn general, humoral immune responses depend critically upon T cell help. In transplantation, prevention or treatment of humoral rejection therefore require drugs that ideally inhibit both B cell and T helper cell activity. Here, we studied the effects of commonly used immunosuppressive drugs [tacrolimus, cyclosporin, mycophenolic acid (MPA) and rapamycin] on T cell helper activity and on T cell-dependent B cell responses. T cells were activated polyclonally in the presence of immunosuppressive drugs in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
102
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(113 citation statements)
references
References 30 publications
10
102
0
1
Order By: Relevance
“…These results indicate that CNIs affect the humoral immune response of patients with transplants by interfering with T helper signals and not by targeting B cells directly. 65 This hypothesis is supported by the study by Struijk et al, 66 which showed that patients with renal transplants who were stable on prednisolone plus CsA failed to develop antibodies against T cell-dependent model antigens but responded normally to T cell-independent antigens.…”
Section: Calcineurin Inhibitorssupporting
confidence: 71%
See 3 more Smart Citations
“…These results indicate that CNIs affect the humoral immune response of patients with transplants by interfering with T helper signals and not by targeting B cells directly. 65 This hypothesis is supported by the study by Struijk et al, 66 which showed that patients with renal transplants who were stable on prednisolone plus CsA failed to develop antibodies against T cell-dependent model antigens but responded normally to T cell-independent antigens.…”
Section: Calcineurin Inhibitorssupporting
confidence: 71%
“…71 The fact that mTOR inhibitors are able to prevent the in vitro production of Ig with equal efficiency when human B cells are cultured with preactivated or not preactivated T cells further shows that mTOR inhibitors, in contrast with CNIs, have a direct effect on B cells. 65,72 This concept is also validated by the results of a recent study that compared the effects of CNI and mTOR inhibitors on B cells from healthy volunteers. Only sirolimus was able to inhibit the proliferation of B cells and their differentiation into plasma cells.…”
Section: Mtor Inhibitorssupporting
confidence: 50%
See 2 more Smart Citations
“…Notably, CD154, also known as CD40L, plays an important role in T cell-dependent B cell proliferation, memory cell formation, and B cell antibody response (23,24). Our results suggest that CsA should be avoided, whenever possible, in patients receiving adoptive immunotherapy with anti-Aspergillus T H 1.…”
Section: Discussionmentioning
confidence: 94%